Transcranial magnetic stimulation modalities for psychiatric disorders: Publication trends from 1985 to 2019. Issue 4 (22nd October 2021) - Matsuda, Yuki; Yamazaki, Ryuichi; Shigeta, Masahiro; Kito, Shinsuke
Abstract: Aim: Transcranial magnetic stimulation (TMS) is a noninvasive brain stimulation technique that shows potential for treating psychiatric disorders. Although several studies have sought to investigate new TMS modalities for the treatment of various psychiatric disorders, no study has yet examined publication trends in research on TMS modalities for psychiatric disorders. This study investigated publication trends in TMS research for 13 psychiatric disorders, including addiction, dementia, major depressive disorder (MDD), and obsessive‐compulsive disorder (OCD), and schizophrenia, as well as 9 TMS modalities, including bilateral stimulation, deep TMS, high‐frequency stimulation, low‐frequency stimulation, and theta burst stimulation. Methods: Articles published in PubMed from 1985 to 2019 were searched to determine the number of published articles for each year in each category using the "Results by year" tool from the PubMed database. Results: Over the past 30 years, an increasing number of articles were published regarding TMS research for the treatment of MDD, addiction, and dementia, which were among those most commonly investigated psychiatric disorders, whereas the number of articles addressing schizophrenia and OCD treated via TMS remained steady since 2015. Regarding TMS modalities, previous high‐frequency stimulation, low‐frequency stimulation, and bilateral stimulation were the most common topics, with research regarding deep TMS and theta burst stimulation having increased since 2000 and 2005, respectively. Conclusion: TMS applications are rapidly developing and becoming increasingly ubiquitous in various psychiatric disorders. Determining publication trends in TMS research can be a useful method for monitoring TMS research interests and applications of new TMS modalities for psychiatric disorders.